2018
DOI: 10.1016/j.jrp.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic features across development: Assessing longitudinal invariance among Caucasian and African American youths

Abstract: Objectives-Psychopathy is associated with severe forms of antisocial and violent behavior in adults. There is also a rapidly growing body of research focused on extending features of adult psychopathy downward to youth. To date however, the degree to which these features can be consistently and comparatively assessed at these younger ages, remains unclear. This study addresses this issue by investigating measurement invariance of underlying features of psychopathy across childhood and adolescence in a racially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Annual assessments of psychopathic features in youth were collected using a short-form of the teacher-reported Childhood Psychopathy Scale (CPSSF; Hawes et al, 2018; Lynam, 1997; Lynam et al, 2009). The CPS, which was originally constructed using items from the Childhood Behavior Checklist (CBCL; Achenbach, 1991) and the Common-Language Q-sort (CCQ; Caspi et al, 1992), was developed to serve as a relatively pure measure of personality and therefore does not include items that tap into more overt antisocial behaviors (Lynam, Caspi, Moffitt, Loeber, & Stouthamer-Loeber, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Annual assessments of psychopathic features in youth were collected using a short-form of the teacher-reported Childhood Psychopathy Scale (CPSSF; Hawes et al, 2018; Lynam, 1997; Lynam et al, 2009). The CPS, which was originally constructed using items from the Childhood Behavior Checklist (CBCL; Achenbach, 1991) and the Common-Language Q-sort (CCQ; Caspi et al, 1992), was developed to serve as a relatively pure measure of personality and therefore does not include items that tap into more overt antisocial behaviors (Lynam, Caspi, Moffitt, Loeber, & Stouthamer-Loeber, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The original CPS has demonstrated associations with other measures commonly used to assess psychopathy, including the Antisocial Process Screening Device (ASPD; Frick & Hare, 2001) (r’s = 0.57–0.61; Bijttebier & Decoene, 2009), the Triarchic Psychopathy Measure (TriPM; Patrick et al, 2009) (r = 0.38; Drislane, Patrick, & Arsal, 2014), the Inventory of Callous- Unemotional Traits (ICU; Frick, 2004) (r = 0.49; Roose, Bijttebier, Claes, Decoene, & Frick, 2009) and the PCL-R across an 11-year span (r = 0.31; Lynam et al, 2007). The current study used a shortened, 14item shortened version of the CPS (Hawes et al, 2018), consisting of items from the standard CBCL Teacher Report Form (TRF; Achenbach & Edelbrock, 1986). This shortened version has previously demonstrated evidence of strong internal consistency across childhood and adolescence, as well as evidence of longitudinal measurement invariance and measurement equivalency across race (see Hawes et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with studies that have explored psychopathy in adult samples, where individual items from psychopathy measures were shown to perform differently among African American v. Caucasian individuals (Cooke and Michie, 2001) and men v. women (Dotterer et al ., 2017). Other recent psychopathy focused research, however, has found little evidence of measurement inconsistiencies across race (Hawes et al ., 2018). As such, additional research is needed to explore whether measures of CU traits are commensurate across sex, race, and age in samples of youth.…”
mentioning
confidence: 99%
“…Despite the need for studies of CU traits to explore potential measurement invariance across important demographic characteristics (i.e. sex, race, age) (Skeem and Cooke, 2010; Frick et al ., 2014 a ; Frick et al ., 2014 b ; Hawes et al ., 2018), remarkably few studies have actually established measurement equivalence of CU trait measures. Drawing on findings from research focused on assessing the construct of psychopathy more broadly, Tsang et al (2014) found that items assessing psychopathic traits showed differential item functioning among Caucasian v. African American boys (Tsang et al ., 2014).…”
mentioning
confidence: 99%